Proceedings of IADC/SPE Drilling Conference 2006
DOI: 10.2523/98924-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation Strategies for the Risk of CO2 Migration Through Wellbores

Abstract: TX 75083-3836, U.S.A., fax 1.972.952.9435. AbstractStoring carbon dioxide (CO 2 ) underground is considered the most effective way for long-term safe and low-cost CO 2 sequestration. This recent application requires long-term wellbore integrity. A leaking wellbore annulus can be a pathway for CO 2 migration into unplanned zones (other formations, adjacent reservoir zones, and other areas) leading to economic loss, reduction of CO 2 storage efficiency, and potential compromise of the field for storage. This CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 7 publications
3
36
0
Order By: Relevance
“…But a severe depletion of calcium on the outer layer is generally observed. Recently, it was shown that the formation of a calcium carbonate-rich layer may retard the leaching phenomenon but does not stop it [2,5].…”
Section: Durability Of Set Cement Pastementioning
confidence: 99%
See 2 more Smart Citations
“…But a severe depletion of calcium on the outer layer is generally observed. Recently, it was shown that the formation of a calcium carbonate-rich layer may retard the leaching phenomenon but does not stop it [2,5].…”
Section: Durability Of Set Cement Pastementioning
confidence: 99%
“…Corrosion of steel induced by acid gas-containing brines is well documented while data on degradation by wet CO 2 or wet H 2 S is more limited [1]. For cementitious materials, there is an abundant literature dealing with deterioration of cement pastes caused by a CO 2 environment [2][3][4][5]. Published data on degradation mechanisms of cement-based materials exposed to H 2 S environments are more scarce [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The pressurization and depressurization phases of the CO 2 experiments follow a well-defined procedure described by Barlet-Gouédard et al (2006).…”
Section: Test Proceduresmentioning
confidence: 99%
“…A number of studies have shown that wellbore cement is susceptible to CO 2 attack, leading to rapid degradation [6,7], whereas other studies indicate that CO 2 penetration and reaction with cement is limited [5,8], and the long-term performance of wellbore cement in a CO 2 -enhanced oil recovery field was good, providing an effective barrier to significant fluid flow for decades [9,10]. Despite numerous previous studies reporting the geochemical and mineralogical alteration of well cement by CO 2 under geologic sequestration conditions [5,8,11], the rate of Portland cement degradation and long-term integrity of wellbore cement material is still in question and under debate.…”
Section: Introductionmentioning
confidence: 99%